The Bacterial Cell Wall Components Lipopolysaccharide and Peptidoglycan Initiate Divergent Local Tissue and Systemic Inflammatory Response Profiles in the Chicken Model - Kristen A. Byrne; Gisela F. Erf (Animals)
The innate immune system plays an important role in the defense against pathogens, whereby the ability to rapidly mount an effective inflammatory response is critical in the elimination/containment of the infection. To better understand the nature of the inflammatory responses to bacterial components in chickens, we used the growing feather (GF) cutaneous bioassay together with blood sampling to examine the local and systemic inflammatory responses initiated by intradermal (i.d.) GF-pulp injection of lipopolysaccharide (LPS) from Salmonella Typhimurium or peptidoglycan (PGN) from Staphylococcus aureus. Three studies were conducted in egg-type chickens between 9 and 15 weeks of age; Study 1 and 2 examined the leukocyte response profiles to a 100-fold dose range of LPS or PGN over 24 h or 7 d, respectively; Study 3 examined the leukocyte- and cytokine mRNA-profiles in pulps in response to LPS and PGN concurrently over 72 h. I.d. injection of LPS stimulated a heterophil and monocyte/macrophage dominated response in both GF-pulps and blood that was resolved by 48–72 h and differed based on dose administered. The inflammatory response stimulated by PGN was characterized by rapid infiltration of lymphocytes in GF-pulps with sustained high levels of T and B cells over 5–7 d and was neither affected by PGN dose nor reflected in the blood. Limited cytokine transcriptome analyses did not reveal differences that could explain the divergent response profiles to LPS versus PGN. More research is needed to understand the mechanisms underlying the divergent inflammatory responses to LPS and PGN in chickens.